Model Student Facilitator and Explaining untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Nugraheni, Aries (Antroposen: Journal of Social Studies and Humaniora, 2022)
Abstract: The purpose of this study to explore social studies learning outcomes with the Student Facilitator and Explaining learning model. The method used a classroom action research approach. The subject of research was 8th grades, 34 students and consist of two classes, namely A and B classes. The results of study were student learning activities increased, in the 1st cycle 56,25%, in the 2nd cycle reaching 86,75%; Teacher activity has increased, in 1st cycle 72%, 2nd cycle reached 87,89%; While student learning outcomes 1st cycle 59,06% has increased in 2nd 83,18%. The conclusion is the facilitator and explaining models has increased both student activities and teachers, also learning outcomes sighnificanly.